Alteration in lipid oxidation of channel catfish during frozen storage in response to ascorbate applications - Thed, Swee T.; Erickson, Marilyn C. (Wiley, 1994)
Channel catfish were treated with ascorbate via metabolic absorption and vacuum tumbling. The fillets were subjected to varying periods (0, 1.5, 3, 4.5, and 6 months) of frozen storage at −6C. When muscle ascorbic acid levels were increased two fold by both methods, TBA-RS values were significantly lower than that of the control after 6 months of storage. Vacuum tumbled fillets with muscle ascorbic acid that increased by four fold were found to be the least stable to oxidation. The possible fate of the ascorbic acid in the fish tissue was discussed.